Purchase intentions of branded sporting goods in Melaka / Muhammad Fathul Bari Mohd Amin - Mohd Amin, Muhammad Fathul Bari (Faculty of Business and Management, 2020)
The advancement of marketing and the effectiveness of spokespersons as opinion leaders do leave a great impact on a certain brand. Plus, to gain customers’ trust is a great challenge to the business in order to change people’s perspective and behaviour and may induce intention towards certain product. The purpose of this research study is to identify the factors that may create an influence towards consumer’s purchase intention of in branded sporting goods specifically among student athlete. The factors that are being examined in this study consist of endorser’s expertise, endorser’s trustworthiness, and brand credibility. Throughout the research period, a quantitative survey has been carried out for the purpose of supporting the initial idea and thinking. These questionnaires were distributed to individuals that may or may not have purchase branded sporting goods. It can be concluded that those three factors which are, the endorser’s expertise, endorser’s trustworthiness, and brand credibility, have had such a significant relationship to consumer’s purchase intention of branded sporting goods.